Transition metal impurities in semiconductors - Kikoin, K. A (World Scientific, 1994)
Includes bibliographical references (p. [327]-336) and index.; This book discusses the theory of the electron states of transition metal impurities in semiconductors in connection with the general theory of isoelectronic impurities. It contains brief descriptions of the experimental data available for transition metal impurities belonging to iron, palladium and platinum groups and for rare-earth impurities in elemental semiconductors (III–IV, II–VI and IV–VI compounds) and in several oxide compounds (TiO2, BaTiO3, SrTiO3). Also included are applications of the theory to the optical, electrical and resonance properties of semiconductors doped by the transition metal impurities. The book presents a theory unifying previously proposed ligand-field and band descriptions of transition metal impurities. It describes the theory in the context of the general theory of neutral impurities in semiconductors and demonstrates the capabilities of this description to explain the basic experimental properties of semiconductors doped by transition metal impurities. A detailed discussion of various experimental results and their theoretical interpretation is carried out